Influence of Nanoparticle Size Distributions on the (in)Stability and Rheology of Colloidal SiO2 Dispersions and HPAM/SiO2 Nanofluid Hybrids - Haruna, Maje Alhaji; Magami, Saminu Musa (Fine Chemical Engineering, 2023)
This study investigated the relationship between variations in the size distribution and the specific surface area of SiO2 nanoparticles and the in(stability) and rheology of their colloidal dispersions and their resulting silica-poly(acrylamide) hybrids. Thus, SiO2 nanoparticles with size distribution in the range 40-173 nm, corresponding to 70-26 m2/g of specific surface area, were used in the studies. The results show a correlation between the average particle size distribution/the specific surface area of silica nanoparticles with the in(stability) and the rheology of their dispersions, such that an increase in the particle size distribution from 40 to 173 nm corresponds to a decrease in dispersion instability index from 0.913 to 0.112. However, in the silica-poly(acrylamide) hybrids, a change in the particle size distribution from 40 to 173 nm corresponds to an increase in the nanofluid instability index from 0.1913 to 0.929. In the hybrid materials, interactions between polymer chains and nanoparticles lead to size-induced stability and rheological behaviour, such that the broadening of the FTIR peak around 1,000 cm-1 in the nanohybrids was related to an Si-O-H bending vibration that arose because of dominating hydrogen bonding arising from the interaction of the hydroxyl groups and the amide groups in the polymer. The rheological characteristics of the hybrid nanofluids show that the relative viscosity and shear sensitivity of the colloidal dispersions or their hybrids can be tailored by the average particle size distribution of the nanoparticles.